2011
DOI: 10.1029/2010je003725
|View full text |Cite
|
Sign up to set email alerts
|

Compositional variability of the Marius Hills volcanic complex from the Moon Mineralogy Mapper (M3)

Abstract: [1] Using the Moon Mineralogy Mapper(M 3 ), we examine the Marius Hills volcanic complex for the first time from 0.46 to 2.97 mm. The integrated band depth at 1 mm separates the mare basalts on the plateau in two units: (1) a strong 1 mm band unit of localized lava flows within the plateau that has similar olivine-rich signatures to those of the nearby Oceanus Procellarum and (2) a weaker 1 mm band unit that characterizes most of the basalts of the plateau, which is interpreted as having a high-calcium pyroxen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 17 publications
2
70
1
Order By: Relevance
“…McCauley ( variations Heather et al, 2003;Besse et al, 2011;Huang et al, 2011). More recently, Lawrence et al (2013) …”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…McCauley ( variations Heather et al, 2003;Besse et al, 2011;Huang et al, 2011). More recently, Lawrence et al (2013) …”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Many earlier researchers studied the compositional variations of Marius Hills volcanic Complex (Weitz and Head, 1999;Heather et al, 2003;Besse et al, 2011;Sunshine et al, 1994;Lawrence et al, 2013). Sunshine et al, 1994 identified two units based on the brightness differences in visible and near infrared ratio images (0.76/0.99 lm, a simplified 1 lm band strength).…”
Section: Compositional Analysismentioning
confidence: 98%
“…Based on approach of Integrated Band depth analysis of M 3 data. Besse et al (2011), classified Marius hills complex region into two major mare units of different volcanic episodes. Large portion of Marius Hills complex region is covered by high-calcium pyroxene mare unit characterized by weaker IBD1000 compared to other mare unit.…”
Section: Compositional Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the new era of lunar explorations, Japan, China, India, and the United States have successfully launched lunar orbiters and gained numerous high-resolution remote sensing images. Imagery acquired by the Terrain Camera (TC) (10 m/pix) onboard Selene-1 and Narrow Angle Camera (NAC) (0.5 m/pix) onboard Lunar Reconnaissance Orbiter (LRO) have provided the opportunity to study the morphology of Marius Hills in detail (Lawrence et al, 2010); Moon Mineralogy Mapper (M 3 ) onboard Chandrayyan-1 gained both high spatial and high spectral resolution imaging spectrometer data and is very useful for the compositional analysis of the plateau (Besse et al, 2011).…”
Section: Introductionmentioning
confidence: 99%